The Role of The Covid-19 Task Force in Increasing Community Legal Awareness About The Implementation of The Health Protocol - Aldira Dwi Yunianto; Dwi Iman Muthaqin (Department of Civic Education, 2021)
This study examines the issue of public legal awareness in implementing health protocols. This study aims to obtain a clear picture regarding the role of the Bandung City Level Covid-19 Handling Task Force in increasing public legal awareness about health protocols. This study uses a mixed approach with descriptive methods. Data was collected by means of interviews, observations, questionnaires, documentation studies, and field notes. Respondents in this study, namely the Bandung City Level Covid-19 Handling Task Force, Bandung City Health Service, Bandung City Satpol PP, Bandung City Police, and Bandung City Community. The results of the study indicate that the role of the Covid-19 Handling Task Force in increasing public legal awareness regarding the application of health protocols has been running quite well, but has not been maximized. This can be seen from the indicators of public legal awareness in the application of health protocols, namely: (1) Community legal knowledge is considered very good, (2) Community legal understanding can be categorized as good, (3) Legal attitudes are considered adequate, and (4) Behavioral patterns The law in complying with health protocols is still low or can be categorized as bad.